Gratitude as an antidote to materialism in young consumers - Battistella-Lima, Suzana Valente; Veludo-de-Oliveira, Tânia Modesto (Frontiers in Psychology, 2024)
Introduction Materialism has consistently been associated with mental health problems, such as depression and anxiety, and with a decline in overall wellbeing. This article seeks to deepen the understanding of whether or not the level of materialism is reduced when a sense of gratitude is instilled and, if so, how. Methods After a thorough literature review, two empirical studies are presented. Study 1 has a quasi-experimental design and a sample of adolescent individuals in a major city in Brazil. Study 2 takes the form of a survey, completed by parents, in the same city. Results Study 1 demonstrates that a gratitude-based intervention can reduce the subjects’ belief that material wealth brings happiness and signifies success. Study 2 suggests that parents who express gratitude have a perception of raising less materialistic children. Discussion These conclusions add to the theory and practice of consumer psychology and responsible consumption, particularly in relation to the behavior of young people, pointing toward ways to reduce excessive consumption through a simple and easily applied intervention: the stimulus of gratitude.